#### Question

If quadratic equation x^{2} – (m + 1) x + 6=0 has one root as x =3; find the value of m and the root of the equation

#### Solution

`x^2 - (m + 1)x +6 =0`

Put x = 3 in the given equation

`(3)^2 - (m + 1)(3) + 6 = 0`

`=> 9 - 3m - 3 + 6= 0`

`=> -3m = -12`

`=> m = 4`

Put this value of m in the given equation we get

`x^2 - 5x +6 = 0`

`=> x^2 - 3x -2x + 6 = 0`

`=> x(x - 3) - 2(x - 3) = 0`

=> (x - 3)(x - 2) = 0

if x - 3=0 or x - 2 = 0

then x =3 or x = 2

∴ 2 is the other root of the given equation.

Is there an error in this question or solution?

Solution If Quadratic Equation X2 – (M + 1) X + 6=0 Has One Root as X =3; Find the Value of M and the Root of the Equation Concept: Quadratic Equations.